If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 5x + -20 Reorder the terms: 5 = -20 + 5x Solving 5 = -20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + -5x = -20 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -5x = -20 + 0 5 + -5x = -20 Add '-5' to each side of the equation. 5 + -5 + -5x = -20 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = -20 + -5 -5x = -20 + -5 Combine like terms: -20 + -5 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| 2(3x+x^2)=0 | | -2(1+8k)=2(8-7k) | | 2=1x+0 | | -109-8x=2x+51 | | Y=2Y(14-10)3+16-4 | | 12+12x=-17+11x | | 3x-45=90-6x | | 2(x-1)=4x-9 | | 18=4x+-22 | | 3x-58=8x+22 | | -2n^2-9n-10=0 | | -9x=-252 | | -6x-52=-11x+98 | | 6(n-9)=-12n+36 | | 5x-62=10x+18 | | -24-6x=-x+41 | | 100-50+50+100-200+100-100= | | 12x+80=-95+5x | | 114-3x=-68+10x | | 2.3x-0.01=1.2 | | x+3y=1036 | | -6x+10=-14-5x | | 100+10=15*x | | -6+x=50 | | 27p=-756 | | 9x-35=28 | | 6c+3y=t | | 78+x=-34-6x | | 9x-35=28solve | | 21-2(6y-3)=20+6y | | 6c+3y=t-5forc | | w/7=-9/12 |